2010
DOI: 10.3788/col20100803.0253
|View full text |Cite
|
Sign up to set email alerts
|

积分球内漫散射光对铷87原子冷却的装载过程研究

Abstract: Cold 87 Rb atom's loading in an integrating sphere with diffuse light is analyzed theoretically and experimentally. The experimental results show that diffuse light cooling has the greatest efficiency to cool the most atoms when the red detuning between the frequencies of cooling light and atom transition is about 3.3Γ (Γ is the natural linewidth, 6.065 MHz). Theoretical analysis using rate equation and numerical calculations on the cold atom number and loading time agree with the experimental results. This in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…We have verified that the oscillations of an atom in the optical potential of another atom kept at a fixed position also results in an increase (decrease) of kinetic energy for positive (negative) detuning. These results of mutual heating or cooling is thus reminiscent of the asymmetry reported in multiplescattering based atom cooling schemes [25][26][27], but differs from previous works on optical binding of dielectric spheres, which did not study the sign of the particles refractive index [14]. We have performed a systematic study of the free to bound states transition and identified the following scaling law for the critical initial temperature T c of this transition:…”
Section: Stability Analyses For =mentioning
confidence: 59%
See 1 more Smart Citation
“…We have verified that the oscillations of an atom in the optical potential of another atom kept at a fixed position also results in an increase (decrease) of kinetic energy for positive (negative) detuning. These results of mutual heating or cooling is thus reminiscent of the asymmetry reported in multiplescattering based atom cooling schemes [25][26][27], but differs from previous works on optical binding of dielectric spheres, which did not study the sign of the particles refractive index [14]. We have performed a systematic study of the free to bound states transition and identified the following scaling law for the critical initial temperature T c of this transition:…”
Section: Stability Analyses For =mentioning
confidence: 59%
“…We stress that the damping observed in the bound state region cannot be associated to a viscous medium as in [6,7]. In our case, the cooling of the relative motion for negative detunging can be understood as Doppler cooling in a multiply scattering regime [25][26][27].…”
Section: Stability Analyses For =mentioning
confidence: 72%
“…4(c)]. The present situation is at odds from the cooling by diffuse light reported for atoms trapped in a reflecting cylinder [28][29][30], where the cooling was achieved in a fully disordered system, and was optimal off resonance ( ≈ −3 ).…”
Section: Cooperative Coolingmentioning
confidence: 62%